Production and acceptance of gamma-aminobutyric acid (GABA)-kimchi using Tetragenococcus halophilus and monosodium glutamate (penghasilan dan penerimaan kimchi yang mengandungi asid gamma-aminobutirik (GABA) menggunakan Tetragenococcus halophilus dan monosodium glutamat0) - Ab Jabar, Fateen Aqlima Haniem; Chong, Shin Yee; Ilham, Zul; Mohd Zaini, Nurul Aqilah; Abd Rahim, Muhamad Hafiz; Zahia-Azizan, Nur Asyiqin; Wan-Mohtar, Wan Abd Al Qadr Imad (Penerbit Universiti Kebangsaan Malaysia, 2025)
The addition of gamma-aminobutyric acid (GABA) to fermented foods has been progressively expanded to produce ‘Superfood’. In this study, Tetragenococcushalophiluswas extracted from soy sauce moromifrom local factory and evaluated for its potential of Gamma-Aminobutyric Acid (GABA) production in kimchi fermentation. There were four different formulations that were fermented for 20 days. Kimchi fermentation was performed on kimchi added with Monosodium Glutamate (MSG) (T1), kimchi inoculated with T. halophilus (T2), kimchi with combined MSG and T. halophilus (T3), and plain kimchi with no additional starter as a control (C), respectively. A spectral HPLC analysis confirmed that the control sample (C) obtained the highest GABA with 10.90 mg/L followed by T2 with 6.02 mg/L, T1 with 5.72 mg/L, and the lowest content of GABA is produced by T3 with 3.74 mg/L. Sensory analysis was performed by a total of 50 panellists examined the colour, flavour, texture, taste, and overall acceptance of kimchi samples. Kimchi with MSG (T1) received the highest scores for overall acceptance including flavour and taste. This study demonstrated the development of GABA-kimchi using T. halophilus and MSG as future food comprising substantial nutritional profile and improved sensory characteristics.